2015
DOI: 10.1002/path.4630
|View full text |Cite
|
Sign up to set email alerts
|

Local effects of human PCSK9 on the atherosclerotic lesion

Abstract: Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9) promotes atherosclerosis by increasing low-density lipoprotein (LDL) cholesterol levels through degradation of hepatic LDL receptors (LDLR). Studies have described the systemic effects of PCSK9 on atherosclerosis, but whether PCSK9 has local and direct effects on the plaque in unknown. To study the local effect of human PCSK9 (hPCSK9) on atherosclerotic lesion composition independently of changes in serum cholesterol levels we generated chimeric mice expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 51 publications
8
153
0
Order By: Relevance
“…Cells-In vivo evidence demonstrated the pivotal role of SOCS3 and STAT3 on lipid metabolism and SREBP-1 transcriptional activity (6,7,37). To verify that a similar response also occurs in our experimental model, we determined the mRNA levels of SREBP-1 target genes, such as FAS and SCD-1 and the levels of apoB.…”
Section: Socs3 Overexpression Induced De Novo Lipogenesis In Hepg2mentioning
confidence: 75%
“…Cells-In vivo evidence demonstrated the pivotal role of SOCS3 and STAT3 on lipid metabolism and SREBP-1 transcriptional activity (6,7,37). To verify that a similar response also occurs in our experimental model, we determined the mRNA levels of SREBP-1 target genes, such as FAS and SCD-1 and the levels of apoB.…”
Section: Socs3 Overexpression Induced De Novo Lipogenesis In Hepg2mentioning
confidence: 75%
“…Therefore, the progression of kidney dysfunction may influence the expression or clearance of circulating PCSK9 levels, or in other words contribute to the change in plasma concentrations of PCSK9. Previous studies have reported that elevated PCSK9 concentrations are strongly associated with increased LDL-C levels and the development of atherosclerosis [8,16,18,19]. Consequently, PCSK9 inhibitors have become a novel therapeutic target for the therapy of hypercholesterolemia, which has been demonstrated to reduce the risk of cardiovascular disease [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it is worth noting that disorders in lipid metabolism can also be observed in patients even in the early stage of kidney dysfunction [5,6]. Recently, proprotein convertase subtilisin/kexin type 9 (PCSK9), a novel protease, has been established as an important regulator in lipid metabolism by regulating low-density lipoprotein receptor expression [7,8] and its gain of mutation can result in elevated low-density lipoprotein cholesterol (LDL-C) and increased risk of CAD [8,9]. Hence, considering the effects of PCSK9 and status of kidney function on lipid metabolism, whether PCSK9 is involved in the different stages of the kidney dysfunction needs to be clinically studied.…”
Section: Introductionmentioning
confidence: 99%
“…67 Recently, Giunzioni et al found that expression of human PCSK9 in LPS-stimulated macrophages increased mRNA levels of the proinflammatory markers, tumor necrosis factor a (TNF-a) and interleukin 1b (IL-1b), and suppressed those of the anti-inflammatory markers, IL-10 and Arg1 in vitro. 68 The PCSK9 is upregulated by oxLDL stimulation in a dosedependent manner in THP-1 (Human acute monocytic leukemia cell line)-derived macrophages. Small interfering RNA (siRNA)-mediated knockdown of PCSK9 suppresses the oxLDL-induced inflammatory cytokine expression.…”
Section: Impact Of Pcsk9 On Inflammatory Pathways In Cavdmentioning
confidence: 99%